Comparison the antifungal effect of licorice and nystatin, invitro study - Fateme Arbabi-Kalati; Mahsa Porzamani (Tehran University of Medical Sciences, 2013)
Background and Aims: Candida Albicance is one of the most common oral opportunistic infection. Antifungal drugs have several side effects as well as bad taste. Licorice is one of the oldest drugs in Iranian traditional medicine. It has antibacterial and antiviral effects; however, there are a few studies about its antifungal. Therefore, this study was designed for in vitro evaluation of the antifungal effect of licorice. Materials and Methods: Candida Albiance (TIMM 2640) was cultured. After licorice extract was prepared, its antifungal effect was compared with that of nystatin using agar diffusion method. Results: Diameter of inhabitation zone was 32.60±0.84 mm in nystatin group and almost zero in licorice groups. There was statistically significant difference between nystatine and licorice extract (P=0.002). Conclusion: Based on the result of this in vitro study, licorice extract did not show any antifungal effect.